Student Perceptions of Police - Claxton, Taylor Leigh (2018)
Police-community relations are a frequently discussed topic in both academe and the media. Many factors are believed to influence individuals’ perceptions and views of law enforcement, including demographic variables (race and socioeconomic status), experiences with law enforcement, and media consumption. With an emphasis in the news and on social media regarding police misconduct or police brutality, this research seeks to inquire about college students' perceptions of law enforcement and racial injustice within the criminal justice system. While controlling for key demographic variables, this project specifically examines how individuals’ personal experiences with law enforcement and their exposure to news media and social media impact their perceptions and attitudes of police or racial injustice in the criminal justice system. Other variables, such as ideological views, obligation to authority, and delinquent behaviors were also analyzed to provide more specific insight into what factors influence student perceptions. Using ordinal logistic regression, researchers analyzed student perceptions of racial injustice in the criminal justice system and police legitimacy. Findings for this study indicate that variables other than standard demographics, contact with law enforcement, and media consumption had a significant impact on student perceptions of police